Ekstraksi berbantu gelombang ultrasonik dan fotodegradasi senyawa antosianin pada tangkai parijoto (Medinilla speciosa Blume) - Bambang Kunarto; Aldila Sagitaning Putri; Binardo Adi Seno (Agroindustrial Technology, University of Trunojoyo Madura, 2024)
Parijoto is an endemic plant widely found on the slopes of Mount Muria, Kudus Regency, Central Java. The local community often consumes parijoto fresh fruit and processes parijoto fruit such as syrup, dodol, candy, and tea. So far, the Parijoto stalk, which weighs 18.19% of the total weight of the parijoto stalk and fruit, has not been widely used, but it has great potential as a source of anthocyanin. Anthocyanin compounds have low stability to temperature and light. For this reason, extraction with a relatively low temperature and faster than conventional methods is required, one of which is Ultrasonic-assisted extraction. Ultrasonic waves produce cavitation bubbles, facilitating solvent penetration so that cell bioactive components can be extracted more effectively. This study aimed to determine the effect of ultrasonic wave-assisted extraction time of parijoto stalk anthocyanin and examine the effect of various light exposure intensities and exposure times (photodegradation) on Parijoto stalk anthocyanin extract. Ultrasonic-assisted extraction of parijoto stalk anthocyanins used a completely randomized design (CRD) with extraction time (5, 10, 15, 20, and 25 minutes) and three treatment repetitions. In photodegradation using a factorial complete randomized design with the treatment of light exposure intensity (2037 lux, 4259 lux, 6482 lux, and 9259 lux) and exposure time (6, 12, 18, and 24 hours). The results showed that the longer the extraction, up to 20 minutes, the total anthocyanin levels, redness (a*), and yellowness (b*) increased while lightness (L*) decreased. The higher the light intensity of the fluorescent lamp and the longer the light exposure, the lower the total anthocyanin content with a lower half-life. Ultrasonic-assisted extraction have proven to be quite effective for the anthocyanin extraction but need to attention with time and light exposure intensity.